Gastrointestinal hemorrhage due to Meckel's diverticulum - Zagia, Miguel; Larre Borges, Uruguay; Cassinelli, Daniel (Cirugía del Uruguay, 1971)
This is a case of digestive hemorrhage caused by a peptic ulcer at the base of Meckel's diverticulum with heterotopic mucosa